Radiation-Induced Chemistry of Carbon Dioxide: A Pathway to Close the Carbon Loop for a Circular Economy - Ramirez-Corredores, Maria M.; Gadikota, Greeshma; Huang, Erin E.; Gaffney, Anne M. (Frontiers in Energy Research, 2020)
Recent advances in modular nuclear reactors could facilitate the use of irradiation to produce fuels and chemicals using anthropogenic CO2. One of the challenges in CO2 conversion reactions is the stability or low reactivity of CO2. Chemical activation of CO2 via thermochemical or electrochemical approaches contributes to the high energy intensity of CO2 conversion reactions. Activation of the CO2 molecule via irradiation at significantly lower temperatures may now allow us to use heterogeneous CO2-bearing waste gas streams and low-carbon emitting nuclear energy resources to produce high value chemicals and fuels in a distributed manner. In this paper, we review the radiolytic behavior of CO2 and particularly, irradiation pathways relevant for producing fuels and chemicals using CO2, technological advances and research directions for advancing radiolytic conversion of CO2 to chemicals and fuels.